1.
a) 2x-(1-4x) = 2 + (8x-5).
b) 4 - 2(5 -x) =x- 4(x- 1)
c) 7 - (3x + 4) = (x + 1) - (2x + 4)
d) x + 3 - (4 -x) = 3x - (2x- 3)
2.
a) x/3 - 5/6 = 1/12 - x/2
b) 7/9 + x/2 = 3/2 - x/18
c) x/2 - 3/4 = 7/8 + x/4
d) x/9 + 1/2 = 5/4 - x/6 + 1/12

Zamiast tych [/] kresek powinna być kreska ułamkowa.

1

Odpowiedzi

2009-04-09T08:48:01+02:00
1.
a)2x-(1-4x) = 2 + (8x-5)
2x - 1 + 4x = 2 + 8x - 5
2x + 4x - 8x = 2 - 5 + 1
-2x = (-2) /:(-2)
x = 1

b) 4 - 2(5 -x) =x- 4(x- 1)
4 - 10 + 2x = x- 4x + 4
2x - x + 4x = 4 - 4 + 10
5x = 10 /: 5
x = 2

c) 7 - (3x + 4) = (x + 1) - (2x + 4)
7 - 3x - 4 = x + 1 - 2x -4
-3x - x + 2x = 1 - 4 - 7 + 4
-2x = (-6) /: (-2)
x= 3

d) x + 3 - (4 -x) = 3x - (2x- 3)
x + 3 - 4 + x = 3x - 2x + 3
x + x - 3x + 2x = 3 - 3 + 4
x = 4

2.
a) x/3 - 5/6 = 1/12 - x/2
4x/12 - 10/12 = 1/12 - 6x/12
4x/12 + 6x/12 = 1/12 + 10/12
10x/12 = 11/12 /*12
10x = 11 /:10
x = 11/10

b) 7/9 + x/2 = 3/2 - x/18
14/18 + 9x/18 = 27/18 - x/18
9x/18 + x/18 = 27/18 - 14/18
10x/18 = 13/18 / * 18
10x = 13 /: 10
x = 13/10

c) x/2 - 3/4 = 7/8 + x/4
4x/8 - 6/8 = 7/8 + 2x/8
4x/8 -2x/8 = 7/8 + 6/8
2x/8 = 13/8 / * 8
2x = 13 /: 2
x = 13/2 = 6½

d) x/9 + 1/2 = 5/4 - x/6 + 1/12
4x/36 + 18/36 = 45/36 - 6x/36 + 3/36
4x/36 + 6x/36 = 45/36 +3/36 -18/36
10x/36 = 30/36 / * 36
10x = 30 /:10
x = 3


prosze bardzo:)
5 4 5